SEFT as an Effort to Overcome the Manifestations of Burnout Syndrome - Zakiyah, Ana (Kirana Publisher (KNPub), 2024)
Burnout syndrome describes a response to chronic work-related stress. One of the techniques to overcome this is the Spiritual Emotional Freedom Technique (SEFT), which combines spiritual power and energy psychology. This study used a literature review with the PICOS framework. Article search using electronic databases: Google Scholar, Research Gate, PubMed, and Science Direct with the keywords